2022
DOI: 10.1590/fst.34021
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous extraction of carotenoids and phenolic compounds from pulps of orange and yellow peach palm fruits (Bactris gasipaes) by ultrasound-assisted extraction

Abstract: Peach palm fruits (Bactris gasipaes) are native to the Amazonia and exhibit high levels of bioactive compounds, especially carotenoids and phenolic compounds. In our study, the ultrasound-assisted extraction (UAE) technique with different solvents [ethanol, ethyl acetate and ethanol/water (1:1, v/v)] was investigated to determine the best conditions for the simultaneous extraction of carotenoids and phenolic compounds from pulps of orange and yellow peach palm fruits to produce extracts with high bioactive com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
0
2
1
Order By: Relevance
“…It was noted that extractions assisted by ultrasound and green solvent presented a lower yield when compared to other conventional extraction methods, such as those that use solvents derived from waste from the petrochemical industry. Studies performing solid-liquid extractions using solvents such as petroleum ether or hexane from peach palm fruits by Santos et al [1], Torres-Vargas et al [31], Monteiro et al [32], and Santos et al [33] (2022) found a higher percentage of lipid extract yield than this study. The choice of the extraction method to be applied must follow parameters that consider factors such as raw material, process efficiency, complexity or simplicity of the extraction method, cost, extraction speed, possibilities of loss or degradation, absence of chemical product waste, quality of the extracted product, and, with regard to this research, its suitability for the principles of green chemistry.…”
Section: Extraction and Yield Of Peach Palm Lipid Extractscontrasting
confidence: 48%
“…It was noted that extractions assisted by ultrasound and green solvent presented a lower yield when compared to other conventional extraction methods, such as those that use solvents derived from waste from the petrochemical industry. Studies performing solid-liquid extractions using solvents such as petroleum ether or hexane from peach palm fruits by Santos et al [1], Torres-Vargas et al [31], Monteiro et al [32], and Santos et al [33] (2022) found a higher percentage of lipid extract yield than this study. The choice of the extraction method to be applied must follow parameters that consider factors such as raw material, process efficiency, complexity or simplicity of the extraction method, cost, extraction speed, possibilities of loss or degradation, absence of chemical product waste, quality of the extracted product, and, with regard to this research, its suitability for the principles of green chemistry.…”
Section: Extraction and Yield Of Peach Palm Lipid Extractscontrasting
confidence: 48%
“…As for carotenoids, it was observed that peach palm flour has a high content of total carotenoids, 2410.00 µg/100g, when compared to the levels reported by Monteiro et al (2022) [35], who reported that orange-colored flour contained more carotenoids than the yellow color, being 105.39 µg/g and 13.89 µg/g respectively. It is worth highlighting that the health benefits of carotenoids are attributed to their bioaccessibility and bioavailability [36].…”
Section: Technological Properties and Antioxidant Activitymentioning
confidence: 55%
“…The technology of application of ultrasonic waves is widely studied and discussed in several areas (Demirci, et al, 2022;Liao et al, 2022;Monteiro et al, 2022) , in recent years ultrasound has become an alternative for improvement in food technology in the processes of marination, freezing, drying, emulsification, inactivation of microorganisms, softening of meats and improved pasta switching (Araújo et al, 2022;Demirci et al, 2022;Liao et al, 2022;Monteiro et al, 2022).…”
Section: Ultrasound Principlesmentioning
confidence: 99%